2022
DOI: 10.1186/s40359-022-00752-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of post-traumatic stress on quality of life and fatigue in women with Gulf War Illness

Abstract: Background Gulf War Illness (GWI) is a chronic, multi-symptomatic disorder characterized by fatigue, muscle pain, cognitive problems, insomnia, rashes, and gastrointestinal issues affecting an estimated 30% of the ~ 750,000 returning military Veterans of the 1990–1991 Persian Gulf War. Female Veterans deployed to combat in this war report medical symptoms, like cognition and respiratory troubles, at twice the rate compared to non-deployed female Veterans of the same era. The heterogeneity of GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…37 Shastry et al (2022) showed the same pattern of results in female veterans. 38 Taken together, these findings suggest that PTSD as a comorbidity identifies a subgroup of GW veterans-including those with GWI-that suffer from a particularly high burden of poor health. This is corroborated by our finding that, among veterans with GWI, those with comorbid PTSD are much more likely to also meet criteria for severe GWI than those without.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…37 Shastry et al (2022) showed the same pattern of results in female veterans. 38 Taken together, these findings suggest that PTSD as a comorbidity identifies a subgroup of GW veterans-including those with GWI-that suffer from a particularly high burden of poor health. This is corroborated by our finding that, among veterans with GWI, those with comorbid PTSD are much more likely to also meet criteria for severe GWI than those without.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, Jeffrey et al (2021) recently showed that GW male veterans with both GWI and PTSD reported worse physical and mental health than veterans with only GWI 37 . Shastry et al (2022) showed the same pattern of results in female veterans 38 . Taken together, these findings suggest that PTSD as a comorbidity identifies a subgroup of GW veterans—including those with GWI—that suffer from a particularly high burden of poor health.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…J. Gifford et al, 2022;Jeffrey et al, 2021), and higher levels of pain and symptoms of depression (E. J. Gifford et al, 2022;Jeffrey et al, 2021;Shastry et al, 2022). Although the etiology of GWI is not completely understood, researchers have hypothesized that it is due to the many military exposures veterans experienced while deployed, which include nerve agents, pyridostigmine (PB) pills, pesticides, depleted uranium, and smoke from oil well fires.…”
mentioning
confidence: 99%
“…Gulf War illness (GWI) is a chronic multisymptom illness that affects veterans who deployed in support of the 1990–1991 Gulf War and is characterized by alterations in mood and cognition, fatigue, and musculoskeletal problems (Fukuda et al., 1998). GWI is a debilitating health condition that is associated with increased health care utilization (Gwini et al., 2017), lower physical and mental health–related quality of life (Fukuda et al., 1998; E. J. Gifford et al., 2022; Jeffrey et al., 2021), and higher levels of pain and symptoms of depression (E. J. Gifford et al., 2022; Jeffrey et al., 2021; Shastry et al., 2022). Although the etiology of GWI is not completely understood, researchers have hypothesized that it is due to the many military exposures veterans experienced while deployed, which include nerve agents, pyridostigmine (PB) pills, pesticides, depleted uranium, and smoke from oil well fires.…”
mentioning
confidence: 99%